Antifungal activity of essential oils of Myrcia ovata chemotypes and their major compounds on phytopathogenic fungi (Bioscience Journal, 2020)
This work evaluated the antifungal activity of essential oils of Myrcia ovata chemotypes (MYRO-175, MYRO-156, MYRO-154, MYRO-165, and MYRO-015) and their major compounds (linalool, geraniol, citral, and (E)-nerolidol) on the phytopathogenic fungi Fusarium pallidoroseum (which causes melon postharvest rot) and Colletotrichum musae (which causes anthracnose in banana). The essential oils were obtained by hydrodistillation and analyzed by GCMS/FID. To evaluate the antifungal activity, the essential oils and their major compounds were tested at different concentrations (0.1; 0.3; 0.4; 0.5; 0.7; 1.0; 3.0, and 5.0 mL/L). The major compounds found in the essential oils were nerolic acid, linalool, geraniol, citral, and (E)-nerolidol. The essential oils of the plants MYRO-154, MYRO-165, and MYRO-015 had the minimum inhibitory concentration (MIC) (0.3 mL/L) for F. pallidoroseum and the lowest minimum fungicidal concentration (MFC) (0.7 mL/L), for C. musae. Geraniol and citral had the lowest MFC (0.5 mL / L) for the two fungi tested. For F. pallidoroseum, the essential oils of the chemotypes were more effective than their major compounds. Conversely, the major compounds geraniol of the chemotype MYRO-156 (74.37%) and citral were more effective than their respective essential oils for C. musae. (E)-nerolidol and geraniol of the chemotype MYRO-015 (33.15%) were responsible for the antifungal activity of the essential oils of their respective chemotypes.